Decentering Attenuates the Associations of Negative Affect and Positive Affect With Psychopathology. (November 2017) - Naragon-Gainey, Kristin; DeMarree, Kenneth G.
Theory on decentering—an observer perspective on one's ongoing internal experiences—suggests that decentering may be a protective factor against extreme affective states in predicting psychopathology. The current studies were the first to empirically test this, using multiple measures of decentering to capture two distinct components. Across three student samples and two clinical samples, we investigated whether trait decentering moderated the relationship of negative affect and positive affect with a variety of internalizing symptoms, as well as with narcissism, mania, and anhedonia. Greater decentering attenuated the associations of negative affect with dysphoria and panic symptoms, in both cross-sectional (Study 1) and ecological momentary assessment (Study 2) designs. Exploratory analyses in a single sample revealed that positive affect interacted with decentering to predict anhedonia and narcissism symptoms. Implications are discussed for understanding the effects of decentering on psychopathology and refining interventions, as well as the conceptualization and assessment of decentering.